Taking a closer look at how higher education students process and use (discrepant) peer feedback. (April 2023) - Van Meenen, Florence; Masson, Nicolas; Catrysse, Leen; Coertjens, Liesje
Abstract: Little is known on how students process peer feedback (PF) and use it to improve their work. We asked 59 participants to read the feedback of two peers on a fictional essay and to revise it, while we recorded their gaze behaviour. Regarding the PF processing subphase, discrepant PF led to more transitions, but only for participants who reported the discrepancy afterwards. Counterintuitively, participants who did not report the discrepancy, showed longer first-pass reading times. Concerning the PF use subphase, dwell time on essay correlated positively with the quality of the revised essays assessed by professors. Participants with a high-quality revision spent more time addressing higher order comments, corrected one or two lower order aspects at a time and proofread in the end, in which they went beyond the suggestions provided in the PF. These insights can be used when designing training to foster students' uptake of (discrepant) PF. Highlights: Gaze behaviour was measured during processing and use of (discrepant) peer feedback. Processing discrepant peer feedback changed participants' gaze behaviour. Participants' revision performance was associated with dwell time on the essay. Revision strategies of participants with a low vs. high-quality revision differed. These findings suggest avenues for training on peer feedback processing and use.